BASINGWERK ABBEY (FLINTS.) AND ITS FOUNDERS: AN EARL, A KING AND A PRINCE*. (1st June 2021) - Tringham, Nigel
The founding of Basingwerk Abbey by Ranulf earl of Chester in the early 1130s was important for consolidating his newly-inherited authority in Tegeingl, a territory contested by both Anglo-Norman and Welsh lords. At the lower end of the Greenfield valley, its very location in an enclosure associated with kings of Mercia delivered a powerful message to English settlers, but the sentiments of the native Welsh were also addressed by the promotion of the cult (albeit probably 'invented') of St Gwenfrewi, centred on a well at the top of the valley. Changes in political control later in the century provided opportunities for Henry II and princes of both Gwynedd and Powys to become patrons of a house which exemplified cultural interchange.